Towards the implementation of breastfeeding-related health services in community pharmacies: Pharmacists' perspectives - Sim, T.; Hattingh, H. Laetitia; Sherriff, Jill; Tee, L. (Elsevier, 2016)
© 2017 Elsevier Inc.Background: The scope of community pharmacy practice has expanded over the years. Pharmacists are now involved in the provision of a range of professional services. Pharmacists have regular contact with breastfeeding women, and are perceived as easily accessible, trusted health advisors. There is limited information on factors needed to be considered when implementing breastfeeding-related services in pharmacies to meet the needs of this population group. Objective: This study aimed to explore community pharmacists' perspectives on the implementation of breastfeeding-related services, the factors to consider and the required implementation strategies in community pharmacies. Methods: The study involved semi-structured interviews with 30 community pharmacists practising in Western Australian. Interviews were audio-recorded and transcribed verbatim to facilitate analysis. NVivo® Version 10.0 was used to aid organisation of qualitative data and thematic analysis. Responses to closed-ended questions were summarised using the descriptive approach. Results: Participants' perceptions about their role in providing breastfeeding-related services in community pharmacies were generally favourable. Participants reported receiving regular enquiries from the public about the use of various medicines during breastfeeding, in particular non-prescription medicines. Most of their knowledge regarding the use of medicines in breastfeeding and breastfeeding in general was a culmination of day-to-day work experience, self-directed continuing professional development, personal or close-contact breastfeeding experience, and university training. Multifaceted efforts including public and professional education, research and development, and government initiatives were identified as essential to facilitate quality use of medicines in breastfeeding, and to increase pharmacists' support of breastfeeding women. Conclusion: Based on the needs and demand, appropriate training and continuing development is warranted so that pharmacists are well-equipped with knowledge regarding the use of medicines in breastfeeding, and breastfeeding in general. There appear to be opportunities for pharmacists to expand their professional services and contribute towards improved care and support of breastfeeding women at primary care level.